Multilingualism in Scholarly Communication: Main findings and future challenges - Leão, Delfim (Septentrio Conference Series, 2021)
The results of the study and the survey conducted on behalf of the OPERAS-P project (Task “Innovative Models of Bibliodiversity in Scholarly Publications”) were concluded in June 2021 and sought to achieve the following objectives: • to prepare a theoretical background to discuss the use of multilingualism in scholarly communication; • to identify, analyse, and understand the innovative dynamics of working practices and knowledge-sharing within linguistically diverse scholarly contexts and research networks; • to identify and analyse the motivations behind these practices (questionnaires/focus groups – how tools may answer to needs); • to formulate recommendations/guidelines for OPERAS and other stakeholders regarding the future implementation of a service aimed at enhancing multilingualism; • to prepare the conceptual design of a platform prototype for a shared translation service at the scholarly communication level (involving publishers, translators, and researchers). This presentation approaches the most important stages of the work done, as well as the main findings and the challenges they pose for future developments and their implementation.